ANALYSIS OF OIL PALM LEAF DAMAGE DUE TO ATTACKS OF THE RHORNY BEETLE (ORYCTES RHINOCEROS) IN THE PLANTING PHASE PRODUCTION AT PT. BINANGA KARYA - Gibran Hadi Pramono; Khairul Rizal; Yusmaidar Sepriani; Yudi Triyanto (RADJA PUBLIKA, 2026)
This study aims to analyze the intensity of rhinoceros beetle (Oryctes rhinoceros) attacks on oil palm leaf sheaths during the Mature Plant (TM) phase at PT. Binanga Karya. The rhinoceros beetle is a major pest of oil palm plants, reducing vegetative growth and potentially impacting crop productivity if not properly controlled. This study was conducted through a field survey using purposive sampling in mature plant blocks. Observed parameters included the number of infested plants, the number of leaf sheath holes, and the level of leaf sheath damage as an indicator of pest attack intensity. The data obtained were analyzed descriptively and quantitatively by calculating the percentage of attack intensity based on the ratio between the number of infested plants and the total sampled plant population. The results showed that rhinoceros beetle attack intensity was mild to moderate, with variations in the level of damage between plant blocks. The leaf sheath damage found generally consisted of bore holes and bite marks at the base of the sheath. Although the attack has not yet caused a significant decrease in production, the presence of this pest still requires vigilance because it has the potential to increase the level of damage if the population is not controlled. Therefore, appropriate and sustainable pest control efforts are needed to maintain plant health and the stability of palm oil production.